Ballistic Beloniformes attacking through Snell's Window. Issue 2 (28th October 2015) - Day, R. D.; Mueller, F.; Carseldine, L.; Meyers‐Cherry, N.; Tibbetts, I. R.
Abstract : Needlefishes (Beloniformes) were observed employing a range of stalking and attacking behaviours to attack schools of bait fishes ranging from the use of tactics common to predatory fishes to a novel behaviour: the use of leaping, aerial attacks. These aerial attacks are suggested to serve two purposes: to extend the attack range of the needlefishes and to reduce their prey's potential for evasion. Furthermore, a third purpose is hypothesized that the needlefishes are taking advantage of Snell's Window, an optical effect which may mask their approach to their prey.